Solution-processed metal oxide dielectric films: Progress and outlook - Lee, Won June; Kwak, Taehyun; Choi, Jun Gyu; Park, Sungjun; Yoon, Myung Han (APL Materials, 2021)
There has been growing interest in the use of the sol-gel approach to form high-quality dielectric materials. Their tailored properties allow for developing functional electronic devices in a scalable and rapid manner. According to physicochemical principles, the displacement and response behavior of charges under an applied external field can manifest in unique dielectric properties, providing useful information to improve the process, design, and quality of electronic devices. Therefore, a systematic and in-depth investigation of the fundamentals of sol-gel dielectrics is necessary. In this Research Update, we present recent advances in various sol-gel-processed dielectric materials and their applications to functional electronic devices. A brief introduction to sol-gel chemistry to form oxide dielectric films and the basis of physical mechanisms under electrical fields are discussed. Along with the dielectric properties, recent achievements of proof-of-concept experiments and their various applications to functional electronic devices are introduced. It is expected that further innovations in solution-processed metal oxide dielectrics will achieve cost-effective high-performance functional electronics in the near future.
Keywords: Dielectrics property; External fields; High quality; Metal oxide dielectrics; Physico-chemicals; Process quality; Response behaviour; Sol-gel approach; Solution-processed; Tailored properties